Preferensi Konsumen Terhadap Pembelian Buah Semangka (Citrullus Vugaris) di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Indonesia - Maria Otang; Yoseph Yakob Da Rato; Sarlina Noni (Jurnal Ilmiah Wahana Pendidikan, 2021)
The development of watermelon plants is widely sought by farmers in rural areas because it has a distinctive taste. Along with the increasing awareness of the community about the importance of a healthy lifestyle by consuming more fruits, the need for fresh fruits is increasing. This study aims to examine the attributes of watermelon which are consumer preferences or preferences in the Garden of Practice, Faculty of Agriculture, University of Nusa Nipa. The basic method in this research is using descriptive method, and its implementation is by survey technique. The research location was chosen purposively. The sample was determined by convenience sampling method (coincidence sample) with a total of 50 respondents. The types of data used are primary data and secondary data. The analysis used is chi square analysis. The results of the chi square analysis showed that all watermelon fruit variables were significantly different at the 95% confidence level. This means that consumer preferences for watermelon are not the same or there are differences in consumer preferences for watermelons. Watermelon which is the consumer's preference is watermelon which has attributes; sweet taste, medium size, soft meat texture. Based on the results of the study, the suggestions that can be given are: producers should better maintain and improve the quality of the taste of watermelon because the fruit taste attribute is the attribute most considered by consumers in choosing watermelon, and should be able to provide more medium sized watermelons. and textured meat is tender.